Scoping study on existing CIS/CSA relevant units/engagements in Democratic Republic of Congo - Karume, Katcho; Ayagirwe, Rodrigue; Ibanda, Angele; Lina, Alexis Alek; Mubalama, Mondo; Chuma, Géant; Bagula, Espoir (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
RUFORUM conducted a scoping study to identify areas of CSA/CIS convergence for member universities from 20th November to March 2022. Consultations were made with the Deans of the Faculties of Agriculture and related disciplines of Congolese member universities in eastern DRC, through zoom and then individual questionnaires to identify the focal persons who are involved in Climate Smart Agriculture teaching and research. Selected staff of the considered universities [Université Evangélique en Afrique (UEA), Université de Kisangani (UNIKIS) and Université Officielle de Bukavu (UOB)] were convened to a three day workshop in Benin, as a side event during the RUFORUM Triennial Conference and Annual General Meeting from 11th to 13th December 2021. A total of Twenty-one (21) CSA and CIS experts representing 9 countries were invited in the meeting. Participants included representatives from Kenya, Zambia, Ethiopia, Democratic republic of Congo, Benin, Burundi, Uganda, Ghana and Zimbabwe. They analysed the causes of low adoption and utilization of CSA practices & CIS tools and identified the different interventions needed to enhance this shortcoming. Seven prioritoes were identified and it was agreed that the proposed priority CSA will be subjected to national wide consultations in the respective countries. Subsequent to the workshop, the experts were tasked to i) review and compile information about CSA and conduct an inventory of existing programmes and courses related to CSA and potential resource persons in the universities in their respective countries; and ii) conduct country specific consultations and consensus building on the priority CSA. At the university/ academic level, various courses and course units with aspects of CSA and CIS are taught in the considered universities. These courses cover a wide range of the proposed clustered priority areas. These are course units offered in both undergraduate and post graduate programmes.